Student's Perspective on the Use of Youtube Platform Tasks in Public Speaking Subject - Wardhani, Nova; Wardani, Ika Desy; Sabartono, Ribut (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
This research will examine students'' perspectives on learning public speaking using the YouTube software due to a exchange in mastering styles that at the start used traditional patterns to on-line studying styles because of the covid 19. In previous research, it was found the effectiveness of learning using video in this study, researchers will explore from the students'' point of view.Phenomenological research student''s perspective they feel that learning public speaking using the YouTube application makes it very easy for them or is very effective in learning public speaking.student''s perspective is very effective but the impact of pademic still leaves discomfort in learning but the existence of this application can be an alternative.